Perancangan Media Pembelajaran Berbasis Aplikasi Kahoot pada Meta Pelajaran Administrasi Sistem Jaringan di SMKN 1 Rao Selatan - Yanti, Syafrina; Zakir, Supratman; Sesmiarni, Zulfani; Iswantir , Iswantir (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research is motivated by several problems that the authors found in class XII SMKN 1 Rao Selatan, especially in the Subject of Network Systems Administration. the obstacle experienced by the teacher during the learning evaluation process is that it is known that the evaluation process is prone to cheating such as students who imitate their friends' answers while doing daily exercises, besides that students are not punctual when submitting daily exercises such as students who are late when collecting daily exercises from the previous day. that has been determined, and practice corrections are still done manually by correcting the answers to the exercises one by one. Therefore, the authors designed learningmedia based on the Kahoot application in the Network Systems Administration Subject so that it can be used as an alternative learning media. The purpose of this research is to produce a valid, practical, and effective Kahoot application-based supporting media design for Network System Administration Learning. The type of research used in this study is the development method or Research and Development (R&D). The development model used is DDD-E consisting of four stages, namely the decide, design, develop, and evaluate stages. The product tests used in this study were validity.